2016
DOI: 10.21608/jpp.2016.45534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rootstocks and Grafting Methods on Watermelon (Citrullus lanatus) Production

Abstract: The present study was carried out at a private nursery in Mansoura city and a private farm at Zayyan region, Belqas district, Dakahlia Governorate during the two summer seasons of 2014 and 2015 to study the effects of different rootstocks and grafting methods on growth, yield and fruit quality of watermelon cv. Aswan F 1. The experiment included thirteen treatments resulted from the combinations of four rootstocks [Jumbo F 1 and Nun 6001 F 1 hybrids (Cucurbita maxima × Cucurbita moschata), Bottle gourd (Lagena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Regarding to, fruit quantity and quality, the different reports worldwide demonstrated that the fruit weight, total and early yields, fruit yield varied depending on both rootstock and scion types. Karaca et al (2012), El-Gazzar et al (2016), El-Kersh et al (2016) and Kombo & Sari (2019). Similar findings were observed in grafted watermelon and confirmed by El-Gazzar et al (2016) and Gómez et al (2017).…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Regarding to, fruit quantity and quality, the different reports worldwide demonstrated that the fruit weight, total and early yields, fruit yield varied depending on both rootstock and scion types. Karaca et al (2012), El-Gazzar et al (2016), El-Kersh et al (2016) and Kombo & Sari (2019). Similar findings were observed in grafted watermelon and confirmed by El-Gazzar et al (2016) and Gómez et al (2017).…”
Section: Introductionsupporting
confidence: 62%
“…Karaca et al (2012), El-Gazzar et al (2016), El-Kersh et al (2016) and Kombo & Sari (2019). Similar findings were observed in grafted watermelon and confirmed by El-Gazzar et al (2016) and Gómez et al (2017). Pulgar et al (2000), Hu et al (2006), Yuan et al (2016), and declared that the NPK concentrations in melon plants could be affected by both the scion and by the rootstockscion interaction.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The variation in number of leaves may also be due to the genetic reason i.e. each cultivar has its own genetic background (El-Gazzar, et al, 2016).…”
Section: Number Of Leaves Per Plantmentioning
confidence: 99%